IMPROVING STUDENTS WRITING IMAGINATIVE TECHNIQUE AT THE FIRST YEAR STUDENT OF SMA NEGERI 17 BULUKUMBA (A CLASSROOM ACTION RESEARCH) - Ahmad Arkam Ramadhani (-)
As for research question is 1. How technique write imagination can improve ability of student in writing deskritip test from to content of technique write imagination at class student early SMA Negeri 17 Bulukumba 2. How technique write imagination can improve ability of student in writing content about understanding of them to article imagine at class early SMA Negeri 17 Bulukumba 3. How technique write imagination can improve livelines of student in writing tes descritive by using theory write imagination at class early SMA Negeri 17 Bulukumba .Class action research (PTK) this  aim to  know improve  of skill writing at  their effective  and student in course of study through technique write this research imagination .is conducted by 2 cycle of each cycle four times meeting with instrument using writing  test. this Research Subject there is 30  student  class early SMA Negeri 17 Bulukumba. Result of research  obtained for the cycle of 1 and 2 there are difference of score that is ,there is final improvement of cycle both . this Research finding indicate that use oft technique writing  imagination can improve ability write diagnostic tes score student 41 becoming 42,83 at first cycle and after revise at  second cycle by applying descritive text reach 68,16 . Minimum successfulness  criterion ( KKM) is 65 where at cycle there is 1 student ( 3.33%) less , 28 student ( 93,33%) student fair,1 ( 3,33%) goodness whereas at cycle to 2 there is 13 student ( 43,33%) goodness and 17(56,66) obtaining very good. This means that tired student efficientcacy of minimum criterion ( KKM) more than semi from them.